3D Porous Honeycomb‐Like CoN‐Ni3N/N‐C Nanosheets Integrated Electrode for High‐Energy‐Density Flexible Supercapacitor. (29th April 2021) - Li, Kunzhen; Zhao, Bangchuan; Zhang, Hui; Lv, Hongyan; Bai, Jin; Ma, Hongyang; Wang, Peiyao; Li, Wanyun; Si, Jianguo; Zhu, Xuebin; Sun, Yuping
Abstract: Transition metal nitrides (TMNs) are considered as potential electrode materials for high‐performance energy storage devices. However, the structural instability during the electrochemical reaction process severely hinders their wide application. A general strategy to overcome this obstacle is to fabricate nanocomposite TMNs on the conducting substrate. Herein, the honeycomb‐like CoN‐Ni3 N/N‐C nanosheets are in situ grown on a flexible carbon cloth (CC) via a mild solvothermal method with post‐nitrogenizing treatment. As an integrated electrode for the supercapacitor, the optimized CoN‐Ni3 N/N‐C/CC achieves remarkable electrochemical performance due to the enhanced intrinsic conductivity and increased concentration of the active sites. In particular, the flexible quasi‐solid‐state asymmetric supercapacitor assembled with CoN‐Ni3 N/N‐C/CC cathode and VN/CC anode delivers an excellent energy density of 106 μWh cm −2, maximum power density of 40 mW cm −2, along with an outstanding cycle stability. This study provides a neoteric perspective on construction of high‐performance flexible energy storage devices with novel metallic nitrides. Abstract : A novel honeycomb‐like CoN‐Ni3 N/N‐C nanosheet is grown on flexible CC via a gentle and efficient method electrode. Such an unique heterostructure nanosheet can possess enhanced intrinsic conductivity and increased concentration of the active sites to achieve remarkable electrochemical performance. When assembling the flexible quasi‐solid‐state asymmetric supercapacitor with a VN/CC anode, the device is well designed with high energy density.